PENGEMBANGAN SOAL MATEMATIKA MENGGUNAKAN KONTEKS BOWLING UNTUK SISWA KELAS VII SMP KURIKULUM 2013 - Susanti, Susanti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to produce a mathematical problem with the PISA model for students using a bowling context that is valid, practical and has potential effects. The research method that will be used is design research with the type of development studies . Data analysis is a qualitative descriptive analysis. The results of this development research are to produce mathematical questions based on higher order thinking skills (HOTS) for VII grade students of junior high school. This research consists of two stages, namely preliminary or preparation and prototiping stage (formative evaluation) which includes self evaluation, expert reviews and one-to-one , small group and field tests . Potential effects of questions can be known from the results of questionnaires and interviews after the field test . The results of the questionnaire and interviews were analyzed whether students considered the question to have a potential effect to improve students' mathematical abilities. In addition, it is also able to attract interest and motivate students so that they are challenged to solve the problems. These questions also provide a stimulus for students to think critically using their own reasoning in their resolution.